The Influence of Financial Technology, Business Innovation, and E-Commerce on MSME Performance (Case Study of MSMEs Fostered by PT. Bukit Asam Tbk) - Efran Merdianto; Dewi Sartika (Indonesian Scientific Publication, 2026)
This study investigates the effects of financial technology, business innovation, and e-commerce on the performance of Micro, Small, and Medium Enterprises (MSMEs). The study adopts a quantitative approach using data from MSMEs fostered by PT. Bukit Asam Tbk, analyzed through the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The findings demonstrate that the utilization of financial technology, innovative business practices, and e-commerce significantly contributes to improving MSME performance. The study highlights that digital adoption and innovation are vital strategies for sustaining competitiveness in the era of digital transformation.